2013
DOI: 10.2355/isijinternational.53.1850
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on and Finite Element Analyses of the Tilting of Fine Steel Wire in Roller Die Drawing

Abstract: Roller die drawing is required for manufacturing low-formability materials such as high-carbon steels into fine wires with a diameter of 500 μm or less because of its characteristic lower friction than conventional die drawing. However, tilting, which is the inclination of the wire under the roll bite, often occurs in fine wires, which degrades their dimensional accuracy. Excessive tilting may generate wrinkling and overfill of the wire; thus, the design of the drawing setup of roller dies for reducing tilting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In the pursuit of environmental sustainability and energy efficiency, there is a growing demand for the fabrication of lightweight components in the automotive, construction, and aerospace industries. Among various strategies, the use of steel wire with reduced cross-sectional area presents a promising approach to achieve weight reduction while conserving metal resources [1,2]. As a crucial material in contemporary industries, a vast quantity of wire rods is employed in diverse applications, from fencing to bridge and hoist cables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the pursuit of environmental sustainability and energy efficiency, there is a growing demand for the fabrication of lightweight components in the automotive, construction, and aerospace industries. Among various strategies, the use of steel wire with reduced cross-sectional area presents a promising approach to achieve weight reduction while conserving metal resources [1,2]. As a crucial material in contemporary industries, a vast quantity of wire rods is employed in diverse applications, from fencing to bridge and hoist cables.…”
Section: Introductionmentioning
confidence: 99%
“…The second pair of rolls applies further deformation and restores the wire to a round shape, as shown in Figure 1. Studies have revealed many beneficial characteristics that suggest the technique is capable of increasing productivity and product quality [1,4]. Moreover, regarding the mechanical properties of the wires, extensive studies [4][5][6][7][8] have been carried out, and it was observed that roller-die drawn wires, when compared against the conventional drawn wires, are featured by a decrease in tensile and yield strengths, considerably lower power consumption, possibility to increase the reduction in the rolling process for each pass without the risk of occurrence of central cracks in the wire.…”
Section: Introductionmentioning
confidence: 99%